Lentigo Maligna: Clinical Presentation and Appropriate Management - Iznardo H; Garcia-Melendo C; Yélamos O (Dove Medical Press, 2020)
Helena Iznardo,1,* Cristina Garcia-Melendo,1,* Oriol Yélamos1,2 1Dermatology Service, Hospital de la Santa Creu i Sant Pau, Universitat Autònoma de Barcelona, Barcelona, Spain; 2Dermatology Service, Centro Médico Teknon – Quirónsalud, Barcelona, Spain*These authors contributed equally to this workCorrespondence: Oriol YélamosDermatology Service, Hospital de la Santa Creu i Sant Pau, Universitat Autònoma de Barcelona, C/Mas Casanovas 90, Block A, 5th Floor, Module 3, Barcelona 08041, SpainTel +34 935537007Fax +34 935537008Email oyelamos@gmail.comAbstract: Lentigo maligna (LM) is a type of melanoma in situ that has distinctive characteristics regarding epidemiology, risk factors and clinical features. In addition, LM has a potential to progress to an invasive tumor with potentially aggressive behavior: lentigo maligna melanoma (LMM). Overall, LM has a very good prognosis, whereas LMM has the same prognosis as other invasive melanomas with similar Breslow thickness. LM/LMM represents a challenging entity not only regarding the diagnosis but also regarding the management. Diagnostic criteria are not well established, and there is an overlap of clinical, dermoscopic and pathological features with other benign pigmented skin lesions such as lentigines, pigmented actinic keratoses or macular seborrheic keratoses. LM/LMM’s common appearance within photodamaged skin makes lesion border identification difficult. Wide excisions are often required, but since LM/LMM typically appears on cosmetically sensitive areas such as the face, sometimes large excisions are not possible nor desirable. In this sense, specialized approaches have been developed such as margin-controlled surgery or image-guided treatment using reflectance confocal microscopy. Other treatments for LM such as cryosurgery, imiquimod, radiotherapy or photodynamic therapy have been proposed, although recurrence/persistence is common. The current manuscript reviews extensively the published data regarding the diagnosis, treatment and management of both complex entities LM and LMM.Keywords: lentigo maligna, melanoma, lentigo maligna melanoma, dermoscopy, dermatoscopy, reflectance confocal microscopy, staged excision, Mohs surgery, imiquimod